Analysis of Stakeholder Attitudes toward Sustainable Tourism Development of Lake Toba Area - Elserida Nababan; Santi Agustina Manalu; Benedikta Anna Haulian Siboro; Yosef Manik (AIBPM Publisher, 2021)
The purpose of this study is to analyze the attitude of stakeholders towards sustainabletourism development in Lake Toba, Indonesia. The indicators used to measurestakeholder’s attitude were adopted from the United Nations World Tourism Organizationand grouped into the human system and ecosystem categories. A total of 361questionnaires were collected from several stakeholders of Lake Toba tourism.Stakeholders’ attitudes were analyzed by multiplying their level of trust in their level ofimportance to the tourism development indicators. The gap between trust andimportance will be mapped on the importance-performance analysis diagram. Theanalysis indicated that the stakeholders' attitude is generally optimistic about the tourismdevelopment in Lake Toba. However, the level of optimism varies among stakeholders.Tourism entrepreneurs and workers have the lowest attitude value compared to localpeople and tourists. Also, stakeholders which have low income or whose income partlyor most comes from the tourism industry or live in the Lake Toba Area are those in thekey priority to consider. They provide the lowest level of trust but provide the highestlevel of importance in development. Decision-makers must give a more serious approachto these stakeholders to get maximum support.